Looking for peptides from rice starch processing by-product: Bioreactor production, anti-tyrosinase and anti-inflammatory activity, and in silico putative taste assessment - Ferri, Maura; Tedeschi, Tullia; Prandi, Barbara; Michelini, Elisa; Calabretta, Maria Maddalena; Babini, Elena; Graen-Heedfeld, Jürgen; Bretz, Karlheinz; Raddadi, Noura; Gianotti, Andrea; Lamborghini, Matteo; Tassoni, Annalisa (Frontiers in Plant Science, 2022)
One of the major challenges for the modern society, is the development of a sustainable economy also aiming at the valorization of agro-industrial by-products in conjunction with at a significant reduction of generated residues from farm to retail. In this context, the present study demonstrates a biotechnological approach to yield bioactive peptides from a protein fraction obtained as a by-product of the rice starch production. Enzymatic hydrolysis, with the commercial proteases Alcalase and Protamex, were optimized in bioreactor up to 2 L of volume. The two best digestates, selected with respect to peptide release and extract antioxidant capacity, were further fractionated (cut-offs of 10, 5 and 1 kDa) via cross-flow filtration. Amino acid composition indicated that most of the fractions showed positive nutritional characteristics, but a putative bitter taste. A fraction obtained with Alcalase enzyme (retentate 8 kDa) exerted anti-inflammatory potential, while the smaller molecular weight fractions (retentate 1-5 kDa and permeate < 1 kDa) were more active in tyrosinase inhibition. The latter were further sub-fractionated by size-exclusion chromatography. From the 15 most anti-tyrosinase sub-fractions, 365 peptide sequences were identified via liquid chromatography coupled with high resolution mass spectrometry. The present data support the possible exploitation of bioactive peptide from rice starch by-product as ingredients into food, nutraceutical, pharmaceutical and cosmetic formulations.